2018
DOI: 10.1590/1981-22562018021.170140
|View full text |Cite
|
Sign up to set email alerts
|

Elderly people receiving care through an aeromedical service

Abstract: Objective: to characterize the care given to the elderly by an aeromedical service in the south of Brazil. Method: a descriptive, cross-sectional and quantitative study was performed. The data were collected from reports of care of the elderly between July 2014 and June 2016, and were analyzed using simple descriptive statistics with numerical measures and descriptive charts. Results: of the 1071 care visits performed, 214 (19.9%) were related to occurrences involving the elderly, the majority of whom were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
8
Order By: Relevance
“…In this study, most older adults lived only with their partner, which is a common condition among older adults (29) ; however, in studies with particular characteristics outlined among the participants, different family arrangements are observed (30) . A study on the perception of older adults and family caregivers regarding the aging process, all older adults interviewed lived with the family caregiver (31) , being a very common condition among older adults with some degree of dependence, especially those older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most older adults lived only with their partner, which is a common condition among older adults (29) ; however, in studies with particular characteristics outlined among the participants, different family arrangements are observed (30) . A study on the perception of older adults and family caregivers regarding the aging process, all older adults interviewed lived with the family caregiver (31) , being a very common condition among older adults with some degree of dependence, especially those older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are not in the habit of attending doctor's offices and performing routine examinations to prevent health problems, among other things, and are therefore more affected by chronic worsening conditions. [6][7][8][9] With respect to the age group, the present study showed a predominance of care among individuals aged 80 years or older (38.4%). These findings are in line with research conducted in the emergency services, which showed that the victims had an average age of 74.2 years with a standard deviation of 9.3 years.…”
Section: Discussionmentioning
confidence: 43%
“…Besides the severity of the injury, the elderly have specific characteristics, such as: decrease of physiological reserves, associated chronic diseases and drugs of continuous use, which demand a differentiated care in relation to their needs. 7 In the face of accelerated demographic aging, there is a need to understand the demands for care required by the elderly population in the context of emergency and pre-hospital services. Through the design of the main characteristics of the event, it becomes possible to subsidize preventive health actions that seek to minimize the occurrence of such incidents among the elderly population, since these have a reduced capacity for recovery, high rates of morbidity, mortality and institutionalization, culminating in high financial and social cost.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in complementary education can also be associated with the need for specific knowledge according to the area of professional integration into the labor market after completion of the undergraduate degree. Thus, nursing care in the air service requires special formation and constant updating to attend to complex and unpredictable situations (3,14,(23)(24) .…”
Section: Discussionmentioning
confidence: 99%